PENINGKATAN MUTU BAHAN PENGISI KERTAS GROUND CALCIUM CARBONATE MELALUI MODIFIKASI DENGAN TAMARIND KERNEL POWDER (QUALITY IMPROVEMENT OF GROUND CALCIUM CARBONATE AS FILLER IN PAPERMAKING THROUGH MODIFICATION WITH TAMARIN KERNEL POWDER) - Ike Rostika; Nina Elyani; Evi Oktavia; Rina Masriani (JURNAL SELULOSA, 2017)
Ground Calcium Carbonate (GCC) as the filler required in paper making that is intended to reduce production costs thus providing a profit opportunity for the paper industry. However the usage of GCC affected decreasing of paper strength and effectiveness of sizing process. In order to reduce the negative effect, this research has been conducted through the modification of filler using Tamarind Kernel Powder (TKP) which is a natural polymer obtained from local tamarind seeds. The results of high performance liquid chromatography (HPLC) analysis, showed that TKP contained 64-68%   xylose, glucose, maltose and arabinose. Filler modification was conducted with mixing the TKP into CaCO3 and addition of cationic polyacrylamide and sodium polyphosphate dispersant at composition ratio of 100: 0.4 : 0.1: 1.0. Filler application with added the retention aid of cationic polyacrylamide 0.1%, resulted the filler retention value on sheet of 26.9 %. The modified filler shows an increase in filler stability and is easy to form emulsions when compared to commercial fillers. Modification of GCC filler with higher number of TKP usage gives increased filler retention value on sheets, improved sheet formation properties and optical properties.ABSTRAKGround Calcium Carbonat (GCC) sebagai bahan pengisi (filler) dalam pembuatan kertas untuk mengurangi biaya produksi sehingga memberikan peluang keuntungan bagi industri kertas, namun peningkatan jumlah GCC dapat berpengaruh pada menurunnya kekuatan kertas dan efektivitas proses pendarihan. Untuk mengurangi pengaruh negatif telah dilakukan penelitian modifikasi filler menggunakan Tamarind Kernel Powder (TKP) yang merupakan polimer alami dari bahan lokal biji asam jawa. Hasil analisis kromatografi cair kinerja tinggi (KCKT) menunjukkan bahwa TKP mengandung silosa 64-68 %, glukosa, maltosa, dan arabinosa. Modifikasi filler dilakukan  dengan  mencampurkan TKP ke dalam  CaCO3 dengan  penambahan  poliakrilamida kationik dan dispersan natrium polifosfat pada komposisi 100 : 0,4 : 0,1 : 1,0. Aplikasi filler dengan penambahan zat peretensi 0,1 % poliakrilamida kationik diperoleh nilai retensi filler pada lembaran 26,9 %. Filler yang termodifikasi menunjukkan peningkatan stabilitas filler dan mudah membentuk emulsi jika dibandingkan dengan filler komersial. Modifikasi filler GCC dengan jumlah TKP yang lebih tinggi memberikan peningkatan nilai retensi filler pada lembaran, peningkatan formasi dan sifat optik lembaran.